A Report on Rusty Pipe Syndrome (Indian Journal of Case Reports, 2025)
Postpartum bloody nipple discharge, which can be completely benign, is often mistaken for malignancy, adding unnecessary stress to the patient and their family members. Awareness of this rare but benign condition, Rusty pipe syndrome, can alleviate stress for both the patient and the treating health-care team. Hence, we elaborate on a case of Rusty pipe syndrome and its management. A 25-year-old G4P1L0A2 delivered a girl weighing 2 kg via caesarean section. In the immediate post-operative period, there was bloody discharge from both nipples. Examination of both breasts revealed no swelling, inflammation, nipple sores, or cracks. The ultrasound of both breasts was normal. Cytological analysis of the breast discharge showed no evidence of malignancy. The patient was counselled and encouraged to continue exclusive breastfeeding. On the 5th post-operative day, the colour of the breast milk returned to normal. Breast milk is considered a golden fluid for the newborn. Understanding this extremely self-limiting and benign condition, known as Rusty pipe syndrome, and providing supportive counselling to the mother can alleviate unnecessary stress and improve breastfeeding outcomes.